Captain Marvel. Volume 7, The last of the Marvels - Thompson, Kelly, 1976- (Marvel Worldwide, Inc., 2022)
"Vacation -- all she never wanted! Carol Danvers and Jim Rhodes have rekindled their relationship (and their vacation plans!) just in time to get a distress call from Carol's half sister -- Lauri-Ell, the Kree Accuser -- that sends the couple on a bit of a detour. And for a trip to outer space, they'll need to pack much more than just their swimsuits! An old darkness has re-emerged -- one that almost brought the Avengers to their knees not so long ago. A twisted Captain Marvel is once again terrorizing the galaxy! And this time it's not Carol Danvers...we're almost sure. But where is Vox Supreme? Prepare for a thrilling fight to the finish as Carol battles to save the legacy of Captain Marvel!"-- Amazon.com.